2008
DOI: 10.21273/hortsci.43.3.825
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological Characteristics Associated with Vase Life of Cut Flowers of Anthurium

Abstract: The vase life of 26 anthurium (Anthurium andraeanum Hort.) cultivars was evaluated in three separate trials. In the first trial, the influence of 12 morphophysiological characteristics of the cut flower on vase life was investigated. Of these, only spathe color and abaxial stomatal density were able to accurately predict vase life. A vase life prediction equation based on abaxial stomatal density, green/not green and white/not white was able to explain the cultivar variation in vase life in two separate trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This conclusion is further supported by experiments showing that application of antitranspiration waxes to anthurium blooms reduces the rate of water uptake during bloom degradation and can extend the vase life by as much as 18 d, although the general pattern of declining water uptake over the initial 20 d remains (Mujaffar and Sankat, 2003;Paull et al, 1985). Furthermore, Elibox and Umaharan (2008) showed that variation in stomatal density partially explained differences in vase life observed in anthurium cultivars.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This conclusion is further supported by experiments showing that application of antitranspiration waxes to anthurium blooms reduces the rate of water uptake during bloom degradation and can extend the vase life by as much as 18 d, although the general pattern of declining water uptake over the initial 20 d remains (Mujaffar and Sankat, 2003;Paull et al, 1985). Furthermore, Elibox and Umaharan (2008) showed that variation in stomatal density partially explained differences in vase life observed in anthurium cultivars.…”
Section: Resultsmentioning
confidence: 98%
“…The mechanisms regulating this variation in vase life are unknown, limiting the ability of breeders to select for this trait. Elibox and Umaharan (2008) found that deterioration of vase life in anthurium is associated with loss of spathe glossiness, spathe wilting, spathe blueing, and necrosis of the spathe and spadix. Spadix necrosis was the first visible indication of deterioration of vase life for most cultivars and hence is the best index for cultivar comparisons.…”
mentioning
confidence: 99%
“…Furthermore, the change in pH was not associated with L* but rather with changes in a* and b*, which mirror changes in color rather than intensity. Loss of vase life in anthurium is as a result of loss of spathe glossiness, spathe, and spadix browning and spathe bluing (Elibox and Umaharan, 2008b;Paull, 1982). Spathe bluing is attributed to an increase in pH from 5.2 to 5.6 caused by an increase in ammonium ions resulting from protein breakdown (Paull et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Spathe size for each accession was calculated by multiplying spathe length by spathe width. Peduncle length was measured as the linear distance from the point of attachment of the spathe to the point of attachment of the stem (Elibox and Umaharan, 2008a).…”
Section: Methodsmentioning
confidence: 99%
“…The angle of the spadix relative to the spathe (spathe carriage) was measured with a protractor from the base of the spadix (Elibox and Umaharan, 2008a). The colors of the spathe, spadix, and peduncle were also recorded using a horticultural color chart (Wilson Color Ltd., U.K.).…”
Section: Methodsmentioning
confidence: 99%